Tactical combat casualty and wound treatment (Skyhorse Publishing, 2016)
Military surgeons must assume a leadership role in combat casualty care in circumstances that are far less than ideal. This handbook provides much of the information needed to tackle these issues and features state-of-the-art principles and practices of forward trauma surgery as used by military physicians in far flung locations around the globe. In this volume you'll learn such integral skills as: * Tactical field care * Field dressing * Applying pressure dressing * Treating burns * Treating inhalation injuries * And more! Tactical Combat Casualty Care and Wound Treatment is the most trusted and up-to-date manual offered by the Department of Defense for military medical personnel in the field.